A critical review on secondary lead recycling technology and its prospect. (August 2016) - Zhang, Wei; Yang, Jiakuan; Wu, Xu; Hu, Yuchen; Yu, Wenhao; Wang, Junxiong; Dong, Jinxin; Li, Mingyang; Liang, Sha; Hu, Jingping; Kumar, R. Vasant
Abstract: This article reviews recent studies on the recycling of spent lead paste and describes novel technologies. Although the pyrometallurgical process has been dominant in the secondary lead recycling processes, there has been growing pressure to achieve sustainable greener recycling methods to address the environmental pollution issues caused by emissions of lead particulates and sulfur oxides in the traditional smelting route. The electrowinning process has been studied for many years, but high energy-consumption and emissions of toxic components such as fluoride compounds have caused concerns and hindered rapid growth in industrial application. In last 10 years, many sustainable and environmental friendly processes, such as paste-to-paste recycling and hydrogen-lead oxide fuel cell method have been proposed for recycling spent lead paste from discarded lead acid batteries. Ultrafine leady oxide could be prepared from spent lead pastes via newly developed novel hydrometallurgical routes, and then applied as active materials in the cathode and the anode for making high-performance lead acid batteries. It is a green alternative for recycling of spent lead acid battery and other secondary lead.